A Randomised, Controlled Study of Different Glycaemic Targets during Gestational Diabetes Treatment: Effect on the Level of Adipokines in Cord Blood and ANGPTL4 Expression in Human Umbilical Vein Endothelial Cells. (14th May 2018) - Popova, P.; Vasilyeva, L.; Tkachuck, A.; Puzanov, M.; Golovkin, A.; Bolotko, Y.; Pustozerov, E.; Vasilyeva, E.; Li, O.; Zazerskaya, I.; Dmitrieva, R.; Kostareva, A.; et al.
Abstract : Our aim was to study the expression of adipokine-encoding genes (leptin, adiponectin, and angiopoietin-like protein 4 (ANGPTL4)) in human umbilical vein endothelial cells (HUVECs) and adipokine concentration in cord blood from women with gestational diabetes mellitus (GDM) depending on glycaemic targets. GDM patients were randomised to 2 groups per target glycaemic levels: GDM1 (tight glycaemic targets, fasting blood glucose < 5.1 mmol/L and <7.0 mmol/L postprandial, N = 20 ) and GDM2 (less tight glycaemic targets, <5.3 mmol/L and < 7.8 mmol/L, respectively, N = 21 ). The control group included 25 women with normal glucose tolerance. ANGPTL4 expression was decreased in the HUVECs from GDM patients versus the control group (23.11 ± 5.71, 21.47 ± 5.64, and 98.33 ± 20.92, for GDM1, GDM2, and controls;p < 0.001 ) with no difference between GDM1 and GDM2. The level of adiponectin gene expression was low and did not differ among the groups. Leptin gene expression was undetectable in HUVECs. In cord blood, leptin/adiponectin ratio (LAR) was increased in GDM2 compared to controls and GDM1 (p = 0.038 ) and did not differ between GDM1 and controls. Tight glycaemic targets were associated with normalisation of increased LAR in the cord blood. ANGPTL4 expression was downregulated in HUVECs of newborns from GDM mothers and was not affected by the intensity of glycaemic control.